Opposing mesoscale flows in a broken midlatitude squall line - Miner, Barbara D., author (Colorado State University. Libraries, 1993)
During the period 14-15 June 1985 a broken line of convection with one primary gap (echo-free) region developed along a cold front passing through the Oklahoma-Kansas Preliminary Regional Experiment for STORM-Central (OK PRE-STORM) domain. Radar and satellite data are presented to provide an overview of the life cycle of the line. Observations from the OK PRE-STORM mesonetwork and upper air soundings are used to document the occurrence of the gap and an associated surface mesolow. The convective line initially developed as two mesoscale convective systems (MCSs) , one in northeast Kansas, the other in the Texas panhandle, along a weak cold front. As the two MCSs matured, convection developed between the wo similar to the broken-line squall line formation described by Bluestein and Jain (1985). Despite strong low-level convergence and strong moisture convergence, an echo-free region remained between the two MCSs throughout the life cycle of the line. The upper level flow pattern along the line of convection showed strong upper level outflow from the two MCSs converging over the echo-free region and strong subsidence in that region from 250 mb to 650 mb. It is hypothesized that the strong mid- and upper level subsidence was the main factor in the lack of convection in the echo-free region. During the mature phase of the line, a surface mesolow developed within the echo-free region. Calculations are made using a form of the hypsometric equation to determine if the presence of the surface mesolow could have been produced by the mid and upper level subsidence found in that region. At 0300 UTC the mesolow was 2 mb lower than the surrounding areas. Calculations show that subsidence warming in the column could account for a drop in pressure of .75 mb. The results of the study show that while strong low-level convergence existed all along the front throughout most of its life cycle, mid- and upper level outflow from the existing MCSs prevented convection in the echo-free region. The resulting subsidence contributed to the formation of the surface mesolow in the echo-free region. This study shows the need for the evaluation of upper-level forcing mechanisms when forecasting the development of thunderstorms along fronts and convergence zones.
Spring 1993.
Also issued as author's thesis (M.S.) -- Colorado State University, 1993.
Keywords: Squall lines; Mesoclimatology; Convection (Meteorology); Fronts (Meteorology)